Factors associated with knowledge on HIV, TB and malaria among pregnant women and their perception of access to RDTs for HIV, TB and malaria in Savannakhet Province, Lao PDR - Vanphanom Sychareun; Viengnakhone Vongxay; Souksamone Thongmyxay; Kongmany Chaleunvong; Jo Durham; Pascale Hancart Petitet (BMC Pregnancy and Childbirth)
Abstract Background Lao PDR continues to experience challenges in combating the treatable and preventable diseases of HIV/AIDS, tuberculosis (TB), and malaria among priority groups. One priority group are pregnant women. Given increased availability of diagnosis and treatment for these diseases, understanding community knowledge and access to these technologies can inform community-based interventions. This study aims to determine the factors associated with knowledge of HIV, TB, and malaria and their access to rapid diagnostic tests for such diseases among pregnant women in remote areas of Lao PDR. Method This cross-sectional quantitative survey explored pregnant women’s awareness of HIV/AIDS/TB and malaria in three remote districts (Phine, Thapangthong, and Atsaphone) in Savannakhet province, Lao PDR. A face-to-face questionnaire was administered to 189 pregnant women. Descriptive and inferential statistics were applied to determine factors associated with pregnant women’s knowledge and perceived access to information and diagnosis for HIV/AIDS/TB and malaria. This study is under the HEALTH project funded by Expertise France. Results Most participants were 28–42 weeks (50.3%) pregnant; the range was 4–38 weeks, with a mean age of 24.3 years old (range: 14–48 years old). Most participants were farmers (94.2%), 54.5% were illiterate, 74.0% were of the Mon-Khmer ethnic group, and 60% had an income lower than the average. Only 56.6% had accessed ANC, 39.1% attended ANC during the first trimester, and only 19.6% had at least four ANC consults. Less than half of the participants demonstrated (45.5% and 42.3%) a high level of knowledge of HIV and TB, respectively, while slightly above half (54.6%) demonstrated a high level of knowledge related to malaria. Slightly higher than half (53.3% and 52.9%) perceived easy access to HIV and TB services, respectively, while 72.5% perceived easy access to malaria. Less than half of the participants felt it was easy to get tested for HIV (46.5%), TB (52.9%), and malaria (72.5%). Very few of the women (1.6%, 2.1%, and 8.5%) reported having had a test for HIV/TB/malaria, respectively. Factors associated with knowledge of HIV were higher household income and attending ANC more than 4 times, while age, number of children under 2 years, and high knowledge of HIV and malaria were associated with knowledge of TB. In addition, factors associated with knowledge of malaria were the number of children under 2 years, high knowledge of HIV, and perceived easy access to malaria tests. Factors associated with perceived easy access to HIV rapid tests and TB tests were high levels of TB knowledge, attending ANC, and high satisfaction with their health. The number of children under 2 years was associated with perceived ease of access to the HIV rapid test. While factors associated with malaria testing were having a high knowledge of malaria and attending ANC more than four times. Conclusion A very low awareness of HIV, TB, and malaria was identified among pregnant women in this study. Strategies to improve the knowledge of HIV, TB, and malaria in Lao PDR should focus on women who live in rural areas, emerging regions with a high incidence of HIV, TB, and malaria, ethnic pregnant women, the poor, and the illiterate. Lastly, efforts are needed to increase access to early detection and prevention of three deadly diseases, such as HIV, TB, and malaria, among pregnant women by increasing their accessibility to rapid diagnostic tests (RDTs) for HIV, malaria, and TB.